2021
DOI: 10.52312/jdrs.2021.140
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of solitary osteochondromas in children: An option to consider in clinical practice

Abstract: Osteochondromas are neoplasm that belong to the family of cartilaginous histogenesis tumors and represent 90% of all forms of exostoses. As most osteochondromas are asymptomatic, underdiagnosis is frequent. Symptomatic forms usually manifest before the age of 20 years, and the most common symptoms are pain and the detection of a bony mass. Herein, we report four cases of spontaneous regression of solitary osteochondromas in the light of literature. We consider that orthopedic surgeons should take into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…[8][9][10] Studies have shown that osteochondromas account for 35% of benign tumors and 10% of primitive bone cancers, making them the most common benign tumors. [2][3][4] Additionally, Kitsoul et al found that isolated osteochondroma formed at the humerus 26%, femur 30%, and tibia 43%. 11 In a study by Stitzman-Wengrowicz, the age range of patients with osteochondroma was 5-15 years, with an average age of 8.8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Studies have shown that osteochondromas account for 35% of benign tumors and 10% of primitive bone cancers, making them the most common benign tumors. [2][3][4] Additionally, Kitsoul et al found that isolated osteochondroma formed at the humerus 26%, femur 30%, and tibia 43%. 11 In a study by Stitzman-Wengrowicz, the age range of patients with osteochondroma was 5-15 years, with an average age of 8.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that osteochondromas account for 35% of benign tumors and 10% of primitive bone cancers, making them the most common benign tumors 2–4 . Additionally, Kitsoul et al.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of initial presentation, the thickness of the cartilage cap on the MRI was related to tumor shrinkage. Spontaneous regression of solitary osteochondromas is a rare phenomenon [ 6 , 11 ]. The precise mechanism of spontaneous osteochondroma resolution is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Durán-Serrano et al reviewed 32 patients with spontaneously regressed solitary osteochondroma [ 11 ]. They found fourteen cases of the distal femur and five cases of proximal humeral osteochondroma regressions likely to occur in the proximal tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation